Nonaccidental poisoning: the elusive diagnosis. Issue 8 (August 1980) - Lorber, J; Reckless, J P; Watson, J B
Abstract : Although nonaccidental poisoning in childhood is now more often recognised, it is still difficult to establish a diagnosis despite correct investigative procedures. In 1978 we were unable, initially, to establish the cause of intermittent episodes of loss of consciousness in a boy admitted to Sheffield Children's Hospital. Subsequently it was conclusively shown that his mother systematically poisoned him with Tuinal (amylobarbitone and quinalbarbitone) both before admission and while he was being treated in the hospital.